Antimicrobial Resistance Profile and Genotypic Characteristics of Streptococcus suis Capsular Type 2 Isolated from Clinical Carrier Sows and Diseased Pigs in China. (3rd May 2015) - Zhang, Chunping; Zhang, Zhongqiu; Song, Li; Fan, Xuezheng; Wen, Fang; Xu, Shixin; Ning, Yibao
Abstract : Streptococcus suis serotype 2 is an important zoonotic pathogen. Antimicrobial resistance phenotypes and genotypic characterizations of S. suis 2 from carrier sows and diseased pigs remain largely unknown. In this study, 96 swine S. suis type 2, 62 from healthy sows and 34 from diseased pigs, were analyzed. High frequency of tetracycline resistance was observed, followed by sulfonamides. The lowest resistance of S. suis 2 for β -lactams supports their use as the primary antibiotics to treat the infection of serotype 2. In contrast, 35 of 37 S. suis 2 with MLS B phenotypes were isolated from healthy sows, mostly encoded by the ermB and/or the mefA genes. Significantly lower frequency of mrp +/ epf +/ sly + was observed among serotype 2 from healthy sows compared to those from diseased pigs. Furthermore, isolates from diseased pigs showed more homogeneously genetic patterns, with most of them clustered in pulsotypes A and E. The data indicate the genetic complexity of S. suis 2 between herds and a close linkage among isolates from healthy sows and diseased pigs. Moreover, many factors, such as extensive use of tetracycline or diffusion of Tn 916 with tetM, might have favored for the pathogenicity and widespread dissemination of S. suis serotype 2.